2015
DOI: 10.3390/agronomy5020239
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon and Nitrogen Stocks of Different Hawaiian Sugarcane Cultivars

Abstract: Abstracts: Sugarcane has been widely used as a biofuel crop due to its high biological productivity, ease of conversion to ethanol, and its relatively high potential for greenhouse gas reduction and lower environmental impacts relative to other derived biofuels from traditional agronomic crops. In this investigation, we studied four sugarcane cultivars (H-65-7052, H-78-3567, H-86-3792 and H-87-4319) grown on a Hawaiian commercial sugarcane plantation to determine their ability to store and accumulate soil carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We found that the process of crop residue decomposition added additional mineral N to the soil N pools. By contrast, the summerfallow system lost soil N during the postharvest period, whereas the cereal monoculture systems had little or no change in postharvest soil N. The soil N dynamics are complicated 40 , and the quantity of soil N can change with many factors 41,42 . In the present study, the largest change in soil N over the postharvest period occurred in the fall 2007 to spring 2008 period when the summerfallow fields lost 63.9 N kg ha −1 , whereas the fields after pulses increased soil N by 25.3 kg ha −1 , and the fields after wheat increased by 18.5 kg ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the process of crop residue decomposition added additional mineral N to the soil N pools. By contrast, the summerfallow system lost soil N during the postharvest period, whereas the cereal monoculture systems had little or no change in postharvest soil N. The soil N dynamics are complicated 40 , and the quantity of soil N can change with many factors 41,42 . In the present study, the largest change in soil N over the postharvest period occurred in the fall 2007 to spring 2008 period when the summerfallow fields lost 63.9 N kg ha −1 , whereas the fields after pulses increased soil N by 25.3 kg ha −1 , and the fields after wheat increased by 18.5 kg ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Sugarcane smut disease was first reported in Natal, South Africa, in 1877 (Mcmartin, ), and hereafter quickly spread to countries worldwide, such as Kenya, Nigeria, Mali, Tanzania, Mauritius and Rhodesia in Africa (Bock, ; Waller, ; Msechu and Keswani, ; Wada, ; Nzioki and Jamoza, ; Ong'Ala et al ., ), Argentina, Bolivia, Brazil, Dominican, Jamaica, Louisiana, Hawaii, Colombia in America and also Australia in 1998 (Byther et al ., ; Comstock and Heinz, ; Hoy et al ., ; Victoria et al ., ; Tirado‐Corbalá et al ., ). In China, smut disease greatly influences sugarcane yield and could cause a huge direct economic loss up to five billion Chinese yuan every year (Shen et al ., ).…”
Section: Introductionmentioning
confidence: 97%